2014
DOI: 10.1111/ane.12230
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and genetic studies in a family with a novel mutation in the sepiapterin reductase gene

Abstract: Objectives -Sepiapterin reductase deficiency is a rare, but treatable inherited disorder of tetrahydrobiopterin and neurotransmitter metabolism. This disorder is most probably underdiagnosed. To date, only 44 cases have been described in the literature. We present the clinical and genetic investigations in a family with a complex movement disorder. Materials and methods -We examined two affected sisters and three healthy family members. The cerebrospinal fluid was analyzed for neurotransmitter and pterins, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 28 publications
0
23
0
2
Order By: Relevance
“…115 Sepiapterin reductase deficiency Most patients with sepiapterin reductase deficiency exhibit a dramatic response to low doses of levodopa, which improves dystonia, spasticity, pyramidal signs, oculogyric crisis, concentration and overall cognitive function. 83,84,87 One study reported a marked improvement in cognitive ability-especially use of language and performance at school-with levodopa treatment in two patients with sepiapterin reductase deficiency, although these children still did not reach normal academic performance for their age. 87 Doses of levodopa (usually in combination with carbidopa) used for treatment of sepiapterin reductase deficiency range from 0.1 mg/kg to 16.0 mg/kg daily; on average, the most effective dose is 3.9 mg/kg daily.…”
Section: Treatmentmentioning
confidence: 99%
See 3 more Smart Citations
“…115 Sepiapterin reductase deficiency Most patients with sepiapterin reductase deficiency exhibit a dramatic response to low doses of levodopa, which improves dystonia, spasticity, pyramidal signs, oculogyric crisis, concentration and overall cognitive function. 83,84,87 One study reported a marked improvement in cognitive ability-especially use of language and performance at school-with levodopa treatment in two patients with sepiapterin reductase deficiency, although these children still did not reach normal academic performance for their age. 87 Doses of levodopa (usually in combination with carbidopa) used for treatment of sepiapterin reductase deficiency range from 0.1 mg/kg to 16.0 mg/kg daily; on average, the most effective dose is 3.9 mg/kg daily.…”
Section: Treatmentmentioning
confidence: 99%
“…The condition is usually autosomal recessive and results from mutations in SPR, which is located at chromosome 2p14-2p12. [80][81][82][83][84] Sepiapterin reductase deficiency is characterized by axial hypotonia, delays in the development of motor function and language, oculogyric crises, muscle weakness, and dystonia. 81,[82][83][84][85][86][87] Patients with mutations in SPR are commonly misdiagnosed with cerebral palsy.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sleep disorders and marked hypersomnolence are also described (Friedman et al 2006). To date, 13 different mutations for 44 subjects have been reported in the database (http://www.biopku.org) (Koht et al 2014). SRD is a potentially treatable inborn error of pterin metabolism with a response to L-DOPA/carbidopa and 5-hydroxytryptophan (5-HTP).…”
mentioning
confidence: 99%